Pemahaman Materi Bangun Ruang dengan Berbantuan GeoGebra - Delia Dwi Arsita; Mufidatul Ummah Nurul Hidayah; Surya Sari Faradiba (Journal of Education and Learning Mathematics Research (JELMaR), 2020)
This study has purpose to explore the use of GeoGebra in understanding concept of building up space. It is based by the fact that the ability to understand building space six grade elementary school in the city of Malang is still low. based on research conducted in the oddest semester of 2019/2020 obtained at least 6 of 10 elementary school students in one of the private elementary schools in Malang city have difficulty to understanding the concept of building space. In this case, it can be seen that the ability of understanding material build space is still not honed well. This research is a qualitative research, the type of this study is case study. The instrument in this study is a test problem related to the building space, and interview guidelines. In this study, the description of data analysis and meaning interpretation of finding is using text analysis. The results show that the subjects easier to understand the concept of building space with GeoGebra, because it uses the subject GeoGebra can see the building in 3D.